An Overview on Reversible Sea Return Electrodes for HVDC Links - Massimo Brignone; Massimo Marzinotto; Daniele Mestriner; Mario Nervi; Paolo Molfino (Energies, 2023)
HVDC electrodes are usually implemented in HVDC links to avoid the installation of a metallic return. Submarine cables, especially those dealing with lengths of thousands of kilometers, are expensive, and high costs of laying are normally expected. Due to the high number of reversible HVDC links, the marine electrodes must be able to withstand both anodic and cathodic operations, which leads to careful considerations in terms of the material to be used. This paper shows the state of the art of the currently installed reversible sea return electrodes, focusing on the type of installation (sea, shore or pond electrodes) and on the material used, from the first plant installed in 1954 up to the more recent ones established during the XXI century. All reported data derive from publicly available sources. Moreover, since nowadays environmental issues are among the most important topics, for each material and for each type of installation, a guideline on the possible interferences caused by marine electrodes with the surrounding environment is proposed.